STRATEGI ANALISIS RISIKO KREDITUR DALAM MENILAI KELAYAKAN PEMBERIAN KREDIT PADA PT. BANK BCA TBK - Sudrajat, Ade; Rivaldi, Rizki; Ashabil, Luqman; Rahmat Sumbara, Ghiffari; Abdulrahman, M Arif; Adhimas Raspati, Raka; Gunardi, Gunardi (LPPM Politeknik Pajajaran ICB Bandung, 2024)
Providing credit is one of the main activities in banking activities that requires careful risk analysis. In this context, creditor risk analysis strategies are crucial for assessing the feasibility of extending credit. In this research, the author explores the strategies used by creditors in analyzing credit risk using a descriptive approach. This approach makes it possible to gain an in-depth understanding of how creditors evaluate creditor risk and what factors are the main focus in the decision-making process. The main theories that form the basis of this research include the concepts of credit risk analysis, portfolio theory, and decision theory. Using this theoretical framework, the authors investigate various methods and tools used by creditors to evaluate creditor risk. The descriptive research method here involves surveys and interviews with creditors from various financial institutions to gain in-depth insight into best practices in creditor risk analysis. The findings here reveal that creditors generally use a combination of qualitative and quantitative approaches to evaluate creditor risk. Factors such as creditor profiles, market conditions, and internal policies of financial institutions are the main considerations in the decision-making process. The conclusion of this research is the importance of developing a holistic and adaptive creditor risk analysis strategy to reduce default risk and improve credit portfolio performance. The author also presents several practical suggestions to increase the effectiveness of creditor risk analysis strategies in assessing the feasibility of extending credit.